Peran Perempuan Dalam Pembangunan Desa Di Dusun 001 Desa Pasar Pedati Kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - Lorita, Evi; Imanda, Antonio; Amin, Bando; Wahyudi, Agusman; Putri, Rahayu; Popytasari, Popytasari (LPPJPHKI Universitas Dehasen Bengkulu, 2022)
Women play a crucial role in village development, encompassing economic, social, and educational aspects. However, in practice, women's involvement still faces various obstacles, ranging from limited market access and low digital technology proficiency to social problems such as high rates of early marriage. This article aims to describe the results of a Community Service (PkM) activity conducted by lecturers and students from Dehasen University, Bengkulu, in Hamlet 001, Pasar Pedati Village, Pondok Kelapa District, Central Bengkulu Regency. The activity was implemented using a participatory approach through observation, interviews, outreach, discussions, and joint solution formulation. The results showed that residents, especially women, were very enthusiastic and highly motivated to improve their capacity. The main problems identified included limited distribution of MSME products, the lack of business legality, low technological proficiency, and family social issues. The agreed-upon recommendations included digital marketing training, product licensing assistance, distribution support through university partners, and access to educational scholarships. This activity demonstrates that women's empowerment based on community participation and digital technology support has significant potential to improve the economic independence and quality of life of rural communities.